Konsep Cantik pada Iklan Cetak Majalah Kartini Tahun 2014 dan Koran Kompas Tahun 1979: Suatu Analisis Semiotik - Dian Natashia (Bina Nusantara University, 2015)
Advertisements, which can be found in daily life, do not just function as the source of the product’s information, but can also create a new connotation about social reality. This research is intended to reveal the form of the connotation about present beauty of Indonesian women that are trying to be conveyed by the advertisers through present advertisements in Kartini magazines. This research is also revealing elements that are used by the advertisers to attract readers’ attention. To see what are the new connotation that are formed in the present advertisements, they will be compared with advertisements in the older generation. This research is using qualitative descriptive method and the data is coming from the wordings that are printed in those advertisements. The data will be described and analyzed with Discourse of Advertising Theory by Guy Cook and Anchoring Connotation Theory by Roland Barthes, and then the result will be conclude. Through Guy’s theory, this research will reveal all the elements that are used by the producers to build the beauty concept. Through Barthes’ theory, this research will show how the advertisers create new connotation. The result of analysis shows that present beauty concept about ideal body is a beautiful body that are radiated from the outer side of the women’s body and good looking. Beautiful face is a face that looks as young as twenty years old girls. Moreover, the result also shows that producers use current social representative where consumers these days like new, instant products that give maximum result. The result also shows consumers’ doubt over unknown products and women’s fear on fat body and aging.